Disability and work in a health and economic crisis: Mitigating the risk of long‐term labour market exclusion for Australians with disability through policy coordination. Issue 1 (23rd June 2021) - Olney, Sue; Devine, Alexandra; Karanikolas, Pan; Dimov, Stefanie; Malbon, Jennifer; Katsikis, Georgia
Abstract: Labour markets around the world are experiencing extraordinary disruption during the COVID‐19 pandemic. The gap in the employment rate between Australians with and without disability is likely to widen, given the entrenched disadvantage of people with disability in the job market. For many, it will compound existing health and economic vulnerabilities. This scenario is troubling from both a human rights and an economic perspective. In this paper, we examine the interface of two policy instruments intended to improve the prospects of people with disability finding and keeping employment in Australia – Disability Employment Services and the National Disability Insurance Scheme – in the lead up to and in the early stages of the COVID‐19 pandemic. Findings from three studies conducted between 2018 and 2020 reveal these instruments are not mutually reinforcing. With a 10‐year National Disability Employment Strategy (NDES) in development under federal government oversight, we argue that more concerted and targeted effort from these services and broader public policies and programs is needed to ensure Australians with disability are not sidelined in the labour market in the wake of the pandemic. Abstract : We examine the interface of two policy instruments intended to improve the employment prospects of people with disability in Australia. Three recent studies reveal these instruments are not mutually reinforcing. More concerted effort is needed to ensure Australians with disability are not excluded from work in the wake of COVID‐19.